Will online counselling work? : effects of different modes of communication on self disclosure and psychological well-being. - Lin, Siping. (2011)
This study compared the rate of self disclosure and psychological well-being in forty-four participants randomly assigned to either three conditions—computer mediated communication (CMC), telephone communication (TC) and face-to-face communication (FTFC). Self disclosure as a possible mediator in the model was also examined. Self disclosure was measured by the number of emotion words used. An improvement in psychological well-being was indicated by a decrease in negative affectivity. Participants in CMC used significantly more emotion words than participants in FTFC but showed no significant difference when compared with TC. All three modes of communication yielded comparable improvement in psychological well-being after the chat session. The mediation model was not supported.